1/9 times 2/2=2/18
2/3 times 6/6=12/18
2/18+12/18+5/18=(2+12+5)/18=19/18=1 and 1/8
A is answer
Answer:
= n - 2
Step-by-step explanation:
Note the difference between consecutive terms is constant, that is
0 - (- 1) = 0 + 1 = 1
1 - 0 = 1
2 - 1 = 1
3 - 2 = 1
This indicates the sequence is arithmetic with n th term
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference
Here a₁ = - 1 and d = 1, thus
= - 1 + n - 1 = n - 2
*Hint: When you have two y's, they could equal each other in order to solve for the x value.
|x^2 -3x + 1| = - (x - 1)
x^2 -3x + 1 = -x + 1
x^2 - 2x + 1 = 1
x^2 - 2x = 0
x (x - 2)
x = 2 and x = 0
Once both of them are plugged in, only x = 2 works so that's the value for x. Now we just plug it in order to solve for y.
y = x - 1
y = 2 - 1
y = 1
(2, 1)
The answer would be C.